Impactos ambientais em área ocupada por necrópole no município de Caçapava do Sul-RS - Fernandes, Gabriel D'Avila (2017)
In the face of population growth, the natural resources are being overused by the inhabitants of the planet. Historically, sites for the allocation of cemeteries were chosen due to their low economic value, and without any previous geological and hydrogeological studies, so that the soil and water could be exposed to several contaminants. The objective of this work was to determine the soil and groundwater contamination potential in the area of influence of the municipal cemetery of Caçapava do Sul, in Rio Grande do Sul. It has a surficial area to the 0,018 km2. In the determination of the physical characteristics of the soil, was carried out by means of the Guelph permeameter and determined the infiltration coefficient in 7 distinct points. The subsurface was also carried out by means of the geophysical technique of electrically conducting the electric resistance, which allows evaluating anomalies in the resistivity values and from this estimate the geological material that composes the subsoil. The use of the GOD system for evaluation of the aquifer pollution vulnerability. The metal concentration present in water and soil were determined using the Inductively Coupled Plasma Atomic Emission Spectrometry and Inductively Coupled Plasma Mass Spectrometry technique. According to the physical characteristics of the soil, a highly permeable soil was identified. In relation to the infiltration coefficient, values range between 21 to 85 L/m2.day. So the physical techniques indicated a wide variability in the constitution of soils, regolith and granite rock. The subsurface of the terrain was investigated in 6 cable sections. Through the resistivities were identified materials from the weathering of granite, consolidated rock and the saturated zone in water and salts beneath of the soil. With the application of the GOD system it was estimated the class of extreme vulnerability to aquifer where the cemetery is implanted. From the chemical characteristics of the groundwater, several elements were below the Limit of Quantification established by the directive Nº 2914/2011 of M.S. The Manganese presented high values, being in disagreement with the quality reference values of the groundwater. The concentrations of the elements present in the soil include Zinc, Copper and Lead, which may come from funeral props such as metal coils of coffins and paints and varnishes used to preserve wood. Barium presented concentrations possibly being of natural origin. Sodium showed elevated concentrations, which may be an indication of soil contamination by cemetery leachate, since it is a solution rich in salts. The soil was classified as class 3 according to CONAMA 420/2009. The results of this work show that the choice of an area for implantation of cemetery activity must be carried out with great care, not only aiming at the lowest financial cost, but also the environmental sustainability. So we conclude that the use of improper areas do not come to compromise the quality of the environment and life of the people living in the vicinity of these places.